Sigmatism in the Prooemium of Nemesianus’ Cynegetica - Kucz, Anna; Gryksa, Edyta (Colloquia Litteraria, 2022)
Phonetic dramatization is an aesthetic procedure used in the late-classical poetics, which aimed at releasing various emotions “in the density of letters itself”. The phenomenon of ancient sigmatism, i.e. the accumulation of consonants in a particular verse of a poem, is going to be outlined at the very beginning of this article. Then sound effects will be discussed, mainly those based on the analysis of sigmatism present in the prooemium of the treaty on hunting entitled Cynegetica. The abovementioned poem was written by Nemesianus, a Carthaginian poet living in the second half of the 3rd century AD. The article is an attempt to determine whether there is any connection between the phonetics and the meaning of the analysed poem. Moreover, the article’s authors would like to answer the question if repeated use of ‘s’ in particular verses of the Cynegetica prooemium proclaims negative events or shocking emotions